Effects of resistance exercise on fatigue and quality of life in breast cancer patients undergoing adjuvant chemotherapy: a randomized controlled trial - Schmidt, Martina; Wiskemann, Joachim; Armbrust, Petra; Schneeweiss, Andreas; Ulrich, Cornelia; Steindorf, Karen (International journal of cancer, 2015)
Multiple exercise interventions have shown beneficial effects on fatigue and quality of life (QoL) in cancer patients, but various psychosocial interventions as well. It is unclear to what extent the observed effects of exercise interventions are based on physical adaptations or rather on psychosocial factors associated with supervised, group-based programs. It needs to be determined which aspects of exercise programs are truly effective. Therefore, we aimed to investigate whether resistance exercise during chemotherapy provides benefits on fatigue and QoL beyond potential psychosocial effects of group-based interventions. One-hundred-one breast cancer patients starting chemotherapy were randomly assigned to resistance exercise (EX) or a relaxation control (RC) group. Both interventions were supervised, group-based, 2/week over 12 weeks. The primary endpoint fatigue was assessed with a 20-item multidimensional questionnaire, QoL with the EORTC QLQ-C30/BR23. Analyses of covariance for individual changes from baseline to Week 13 were calculated. In RC, total and physical fatigue worsened during chemotherapy, whereas EX showed no such impairments (between-group p = 0.098 and 0.052 overall, and p = 0.038 and 0.034 among patients without severe baseline depression). Differences regarding affective or cognitive fatigue were not significant. Benefits of EX were also seen to affect role and social function. Effect sizes were between 0.43 and 0.48. Explorative analyses indicated significant effect modification by thyroxin use (p-interaction = 0.044). In conclusion, resistance exercise appeared to mitigate physical fatigue and maintain QoL during chemotherapy beyond psychosocial effects inherent to supervised group-based settings. Thus, resistance exercise could be an integral part of supportive care for breast cancer patients undergoing chemotherapy.